2007
DOI: 10.1074/jbc.m609458200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mechanism and Photoprotective Function of Water-soluble Chlorophyll-binding Protein

Abstract: A water-soluble chlorophyll-binding protein (WSCP) is the single known instance of a putative chlorophyll (Chl) carrier in green plants. Recently the photoprotective function of WSCP has been demonstrated by EPR measurements; the light-induced singlet-oxygen formation of Chl in the WSCP tetramer is about four times lower than that of unbound Chl. This paper describes the crystal structure of the WSCP-Chl complex purified from leaves of Lepidium virginicum (Virginia pepperweed) to clarify the mechanism of its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
216
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(238 citation statements)
references
References 41 publications
20
216
0
2
Order By: Relevance
“…2B). It was therefore unlikely that MP-4 belongs to the WSCP class because these proteins are normally tetrameric (37). Using mass spectrometry, the molecular mass of MP-4 was found to be 20.9 kDa (Fig.…”
Section: Fractionation Of Proteins From Seeds Of M Pruriens-ammo-mentioning
confidence: 99%
“…2B). It was therefore unlikely that MP-4 belongs to the WSCP class because these proteins are normally tetrameric (37). Using mass spectrometry, the molecular mass of MP-4 was found to be 20.9 kDa (Fig.…”
Section: Fractionation Of Proteins From Seeds Of M Pruriens-ammo-mentioning
confidence: 99%
“…Interestingly, BnD22 is a class II WSCP that is able to bind chlorophyll (Chl a/b) and chlorophyll precursors such as chlorophyllides a and b in tetrameric forms (Nishio and Satoh, 1997;Schmidt et al, 2003;Horigome et al, 2007). It has been proposed that WSCP as a chlorophyll carrier implied either chlorophyll degradation (Satoh et al, 1998) or chlorophyll biosynthesis (Schmidt et al, 2003;Reinbothe et al, 2004).…”
Section: Meja (mentioning
confidence: 99%
“…This WSCP is able to bind chlorophyll molecules, suggesting a role as a chlorophyll carrier (Satoh et al, 2001;Reinbothe et al, 2004) and an involvement in the regulation of both the development and senescence of chloroplasts. Recently, Horigome et al (2007) have suggested this WSCP may contribute to the photoprotection of chlorophyll molecules.…”
mentioning
confidence: 99%
“…Class-II WSCPs are watersoluble and possess a molecular weight of about 20 kDa. Up to now, a crystal structure obtained by X-ray diffraction is available only for WSCP from Lepidium virginicum [9]. However, all class-II WSCPs occur in tetrameric form binding 1-4 chlorophyll molecules.…”
Section: Introductionmentioning
confidence: 99%